Study of Some Adsorbents for Sampling and Anlsysis of Several Volatile Organic Compounds - Kilic, Naciye; Atalay, Ilknur (Asian Journal of Chemistry, 2010)
In this study, the effect of concentration on some critical thermal desorption parameters such as desorption temperature, desorption time and cold trap temperature were evaluated and compared when using tenax TA and anasorb CMS for the sampling and analysis of acetone, benzene, toluene, methylethyl ketone, tetrachloroethylene and styrene at low and high concentration levels.